An additive-free silicon anode in nanotube morphology as a model lithium ion battery material - Zhuo, Ying; Sun, Hong; Uddin, Md. Helal; Barr, Maissa; Wisser, Dorothea; Roßmann, Philip Kazys; Esper, Julian Duane; Tymek, Sarah; Döhler, Dirk; Peukert, Wolfgang; Hartmann, Martin; Bachmann, Julien (Electrochimica Acta, 2021)
Ordered arrays of parallel, cylindrical silicon nanotubes are obtained by aluminothermic reduction of SiO2 nanotubes generated by atomic layer deposition (ALD) on nanoporous aluminum oxide templates. The reduction to amorphous Si (a-Si) is characterized by a combination of X-ray diffraction (XRD), solid-state cross-polarization magic-angle spinning nuclear magnetic resonance (29Si CP-MAS NMR), ultraviolet-visible spectroscopy, attenuated total reflectance infrared spectroscopy (ATR-IR), and X-ray photoelectron spectroscopy (XPS). These a-Si nanotube arrays are electrochemically active in a lithium-ion battery environment when prepared on Cu current collectors without any additives. The absence of the traditional additive carbon black, which is an electrochemically inert conductor, increases the proportion of capacity associated with faradaic reactions (Li incorporation) with respect to the capacitive component. Electrochemical impedance spectroscopy (EIS) and charge-discharge tests demonstrate that the nanotube morphology yields an improved tolerance to fast cycling.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Aluminothermic reduction; Anode material; Atomic layer deposition; Lithium ion battery; Si nanotube

Ordered SnO2 nanotube arrays of tuneable geometry as a lithium ion battery material with high longevity - Zhuo, Ying; Tymek, Sarah; Sun, Hong; Barr, Maissa; Santinacci, Lionel; Bachmann, Julien (Nanoscale Advances, 2020)
Ordered arrays of straight, parallel SnO2 nanotubes are prepared by atomic layer deposition (ALD) on inert 'anodic' aluminum oxide porous membranes serving as templates. Various thicknesses of the SnO2 tube walls and various tube lengths are characterized in terms of morphology by scanning electron microscopy (SEM), chemical identity by X-ray photoelectron spectroscopy (XPS) and phase composition by X-ray diffraction (XRD). Their performance as negative electrode ('anode') materials for lithium-ion batteries (LIBs) is quantified at different charge and discharge rates in the absence of additives. We find distinct trends and optima for the dependence of initial capacity and long-term stability on the geometric parameters of the nanotube materials. A sample featuring SnO2 tubes of 30 µm length and 10 nm wall thickness achieves after 780 cycles a coulombic efficiency of >99% and a specific capacity of 671 mA h g-1. This value represents 92% of the first-cycle capacity and 86% of the theoretical value.
CRIS-Team Scopus Importer:2020-04-28

Shape-anisotropic cobalt-germanium-borate glass flakes as novel Li-ion battery anodes - Esper, Julian Duane; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; de Ligny, Dominique; Bachmann, Julien; Peukert, Wolfgang; Romeis, Stefan (Powder Technology, 2020)
Novel CoO-Li2O-B2O3 and CoO-GeO2-Li2O-B2O3 flake-like glass particles for battery applications are produced by an innovative technique: Glasses from melt quenching are processed into micron-sized glass flakes in a stirred media mill. Processing under well-controlled conditions yields flake-like particles with high aspect ratios which are suitable for anodes in Lithium-ion batteries. Electrochemical characterization by cyclic voltammetry, electrochemical impedance spectroscopy, galvanostatic charge/discharge cycles and rate capability measurements indicates that the flakes show superior electrochemical properties compared to the bulk glass counterparts with a stable specific capacity of 620 mAh g−1 after 100 cycles. The majority of charge is stored by Li+ ion diffusion inside the material and impedance spectroscopy shows enhanced lithium ion diffusion capabilities of the flakes. The proposed fabrication process is performed under ambient conditions and is simple, cost-efficient, fully scalable and can be easily transferred to other glass compositions with electrochemically active metal oxide
Keywords: Anode; Particle design; Glasses; Shape-anisotropy; Lithium-ion battery

SiO2–GeO2 Glass–Ceramic Flakes as an Anode Material for High-Performance Lithium-Ion Batteries - Esper, Julian Duane; Maußner, Felix; Romeis, Stefan; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; Bachmann, Julien; Peukert, Wolfgang (Energy Technology, 2022)
The preparation of a flake-like glass–ceramic anode material comprised of SiO2 and GeO2 for Li-ion batteries (LIBs) is demonstrated. The precursor glass material is prepared via a traditional melt quenching technique. Flake-like glass particles are obtained by compression in the liquid phase via ball milling. A subsequent heat treatment induces crystallization of GexSiyO6 domains inside the vitreous SiO2–GeO2 matrix. This novel glass-ceramic material is applied as an anode material for LIBs and shows a stable reversible capacity of 520 mAh g−1 at 0.2 C combined with good capacity retention of 87% after 100 cycles. This cycling stability can be attributed to the synergistic effects of having nanocrystalline domains embedded in the glass matrix: The open glass network can withstand the volume change and stress caused by the lithium insertion during cycling, while the nanocrystals act as active sites for the electrochemical conversion and alloying reactions. The glass–ceramic anode material exhibits superior electrochemical properties compared to its pure glass counterparts.
CRIS-Team Scopus Importer:2022-06-10
Keywords: anodes; flake-like particles; glass ceramics; lithium-ion batteries; shape-anisotropy; thermal annealing